The Process of Shaping Consumer Protection in European Union Law: Source Review - Jolanta LORANC-BORKOWSKA (Communications of International Proceedings, 2025)
Consumer protection in European Union law remained on the margins of Community policy for a long time, which stemmed from the prevailing belief in the effectiveness of free market mechanisms and the rationality of the consumer. The initial actions of Community institutions in this area lacked a treaty foundation. It was only in the late 1980s that consumer protection was incorporated into primary law as an autonomous objective of Community policy. From that moment on, protective regulations began to be introduced. The article presents the process of shaping the normative dimension of consumer protection in the European Union. Using the dogmatic and legal method, it discusses the development of consumer rights protection, including EU consumer programmes and the most important consumer directives. Furthermore, it describes the impact of consumer directives on the legal systems of the European Union Member States. The analysis of EU law in the field of consumer rights protection leads to the conclusion that the continuous amendments, repeals, and replacements of existing provisions with new, increasingly detailed regulations do not foster legal stability. Moreover, the excessive complexity of consumer directives, which often employ language incomprehensible to the average consumer, may burden consumers with the need to remember too much information. As a result, this gives rise to legal and practical problems, as it may lead to consumers’ misunderstanding of the provisions and, consequently, to the failure of these provisions to fulfil their intended protective function. Thus, the directive does not appear to be an effective legislative instrument.
Keywords: EU consumer policy; EU consumer directives; consumer rights